Turbulent heat transfer enhancement in a heat exchanger using helically corrugated tube - Pethkool, S.; Eiamsa-ard, S.; Kwankaomeng, S.; Promvonge, P. (My University, 2011)
The augmentation of convective heat transfer in a single-phase turbulent flow by using helically corrugated tubes has been experimentally investigated. Effects of pitch-to-diameter ratio (P/DH=0.18, 0.22 and 0.27) and rib-height to diameter ratio (e/DH=0.02, 0.04 and 0.06) of helically corrugated tubes on the heat transfer enhancement, isothermal friction and thermal performance factor in a concentric tube heat exchanger are examined. The experiments were conducted over a wide range of turbulent fluid flow of Reynolds number from 5500 to 60,000 by employing water as the test fluid. Experimental results show that the heat transfer and thermal performance of the corrugated tube are considerably increased compared to those of the smooth tube. The mean increase in heat transfer rate is between 123% and 232% at the test range, depending on the rib height/pitch ratios and Reynolds number while the maximum thermal performance is found to be about 2.3 for using the corrugated tube with P/DH=0.27 and e/DH=0.06 at low Reynolds number. Also, the pressure loss result reveals that the average friction factor of the corrugated tube is in a range between 1.46 and 1.93 times over the smooth tube. In addition, correlations of the Nusselt number, friction factor and thermal performance factor in terms of pitch ratio (P/DH), rib-height ratio (e/DH), Reynolds number (Re), and Prandtl number (Pr) for the corrugated tube are determined, based on the curve fitting of the experimental data. © 2010 Elsevier Ltd.
Keywords: Friction factor; Heat exchanger; Heat transfer enhancement; Helically corrugated tube; Thermal performance